Experiential Function in Students’ Writing Recount Text - Muhammad Fauzi Romadhon Marpaung; Raden Sri Ayu Ramadhana; Defri Rahmat; Mesra Wati Ritonga; Shabrina Rasyid Munthe (Journal on Education, 2024)
The research was aimed to find out the experiential function in recount text of MA Ar-Royyan students. This research was conducted by qualitative data analysis. The subject of this study were the students of MA Ar-Royyan. They were as the source of the data in the research. The data was the recount text of the students’ writing assignment of tenth grade of MA Ar-Royyan. The conclusion in the study were: in term of ideational meaning analysis indicates that the students‘ recount texts draw on the students‘ experience in particular place and time. The occurrence of process, participants and circumstances are exist in the students‘ recount texts. From the text, there are some process that were realized in the students‘ recount texts such as material, mental, existential, relational process. Not all of the process existed in the students’ text. They used some circumstances such as extent, location, manner and accompaniment. In term of ideational meaning, the process drives the students to choose the right vocabularies in composing their texts. Then from the textual meaning, the students are able to coherent the paragraph in their texts.